2012
DOI: 10.1108/17539261211250726
|View full text |Cite
|
Sign up to set email alerts
|

The role of Smart Home in Smart Real Estate

Abstract: PurposeThe purpose of this paper is to review an emerging type of dwelling, indicated as Smart Home, with a focus on future user lifestyles and needs. Trends toward sustainability and technological changes dramatically alter the concepts of Smart Home. Consequently, real estate decisions are going to be affected by the Smart Home development. Inspired by research in the field of user centered design and future lifestyles, the authors redefine the housing design to increase the acceptance of Smart Homes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…There is the need for widespread campaign by all agencies concerned with the advancement of smart buildings. Developers, investors and property managers and occupiers should be educated on the various elements of smart buildings to avoid what Allameh et al (2012) termed "a mismatch between end users demands and smart home possibilities".…”
Section: Resultsmentioning
confidence: 99%
“…There is the need for widespread campaign by all agencies concerned with the advancement of smart buildings. Developers, investors and property managers and occupiers should be educated on the various elements of smart buildings to avoid what Allameh et al (2012) termed "a mismatch between end users demands and smart home possibilities".…”
Section: Resultsmentioning
confidence: 99%
“…This is an amalgam of user-centred, sustainable and innovative technologies for managing real estate resources efficiently in an urban area, whereby the key information is made available to consumers, managers and agents. The technologies and systems must be sustainable, user-centred and innovative, thereby disrupting traditional practices [28,34].…”
Section: Smart Real Estate (Sre)mentioning
confidence: 99%
“…There are also smart furnishings, with embedded computers that are interconnected and thus allow easy and flexible moving. These may be sensitive to user preference, responsive and programmable; they are interactive due to touchscreens and multifunctional, enabling virtual activities, entertainment and environment control [34]. Similarly, there are smart living spaces and smart garages.…”
Section: User-centrednessmentioning
confidence: 99%
“…If such a pan is sold to a customer in China, the pan may not be able to provide the expected cooking support. The analyses by the researchers in Reference [122] showed that current smart furniture sustainability and innovative trends may not stop anytime soon, and will likely continue to evolve to draw even further development. As such, the authors predict likely changes in smart home innovative trends, which shall be driven by smart furniture.…”
Section: Discussionmentioning
confidence: 99%